Conspectus of effectiveness of the jasper model in developing symbolic play skills for children with autism spectrum disorders - Thi, Tan Nguyen; Thi, Thao Do; Binh, Nga Giap (World Journal of Vocational Education and Training, 2024)
This study provides an overview of 20 research articles from international databases (PubMed, Scholar, Eric, and APA) assessing the effectiveness of the JASPER model in developing symbolic play skills among children with autism spectrum disorders (ASD). The researchers reviewed studies to examine the impact of the JASPER model on the frequency, diversity, and level of symbolic play skills in children with ASD. Results indicate that the JASPER model effectively increases symbolic play skills among children with ASD, enhancing their play experience quality. The application of the JASPER model in developing symbolic play skills for children with ASD in Vietnam shows promise. However, considering differences in intervention services and cultural contexts, recommendations are provided for adapting the JASPER model for effective implementation in Vietnam. This includes cultural adjustments and modifications to intervention protocols. Collaborative efforts between researchers, practitioners, and policymakers are crucial for the successful implementation and dissemination of the JASPER model in Vietnam, potentially improving outcomes for children with ASD in the country.